Potential Improvement in a Portable Health Clinic for Community Health Service to Control Non-Communicable Diseases in Indonesia - Hanifah Wulandari; Lutfan Lazuardi; Nurholis Majid; Fumihiko Yokota; Guardian Yoki Sanjaya; Tika Sari Dewi; Andreasta Meliala; Rafiqul Islam; Naoki Nakashima (Applied Sciences, 2023)
The COVID-19 pandemic has limited routine community health services, including screening for non-communicable diseases (NCDs). An adaptive and innovative digital approach is needed in the health technology ecosystem. A portable health clinic (PHC) is a community-based mobile health service equipped with telemonitoring and teleconsultation using portable medical devices and an Android application. The aim of this study was to assess the challenges and potential improvement in PHC implementation in Indonesia. This study was conducted in February–April 2021 in three primary health centers, Mlati II in Sleman District, Samigaluh II in Kulon Progo, and Kalikotes in Klaten. In-depth interviews were conducted with 11 health workers and community health workers. At the baseline, 268 patients were examined, and 214 patients were successfully followed-up until the third month. A proportion of 32% of the patients required teleconsultations based on automatic triage. Implementation challenges included technical constraints such as complexity of applications; unstable networks; and non-technical constraints, such as the effectivity of training, the availability of doctors, and the workload at the primary health center. PHCs were perceived as an added value in addition to existing community-based health services. The successful implementation of PHCs should not only be considered with respect to technology but also in terms of human impact, organization, and legality.